Pengembangan Media Pembelajaran Berbasis Android dalam Pembelajaran Jarak Jauh untuk Guru Biologi Tersertifikasi - Nurkamilah, Siti; Muthmainnah, Rifaatul (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This research was conducted to develop an Android-based learning media that is innovative and easy to use by teachers who have been certified in distance learning. The research method used is the Research and Development research method, the development stage refers to the Borg and Gall design which only focuses on 9 steps, namely potential and problem analysis, data collection, product design, design validation, design revision, product testing, product revision, testing. user trial and product revision. Respondents in this study were biology teachers from high school and Madrasah Aliyah in Garut Regency who were certified as well as media and material experts. The results of the study show that android-based learning media is feasible to be developed, this is evidenced by the obtained average score of 3.6 in the good category. In conclusion, android-based learning media can be an alternative learning media that is effective, efficient, interesting, and can be used anywhere and anytime and can be used by teachers, especially Biology teachers who have been certified and are not yet so skilled in making learning media for use in learning. long distance. Keywords: Certified Biology Teacher, Android-Based Learning Media, Distance Learning